Analisis Perbandingan Aplikasi Google Maps, Wisepilot, dan Here Wego Dengan Pendekatan User Centered Design (UCD) dan Kaidah Cartography - Oki Ari Saputra; Fatwa Ramdani; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Application testing is measured from the user's point of view by highlighting five aspects of testing, which are functionality, effectiveness, efficiency, reliability, usability, and cartography. In the functionality aspect, a function test is performed on each application, on the aspect of efficiency is done to obtain page speed grade in each application that is examined using Pingdom and GTMetrik tools, on the reliability aspect is monitored on each server using the Pingdom tool for 30 day, the usability aspect was evaluated using a questionnaire to find out user satisfaction in each application, and in the aspect of cartography an evaluation of the map in each application was based on cartography rules.This research aims to make a comparison between Google Maps, Here Wego, and Wisepilot applications on Android operating systems as a better alternative that should be used in searching locations on maps and navigation routes through user satisfaction testing. Applications in this test are used in the recommended navigation routes and locations in Malang which requiring several types of testing on each application. For each application is tested and evaluated by five aspects of testing using Web Quality Evaluation Method (WebQEM) method and cartography rules. The writer's analysing and make a comparison of test results that are conducted on each aspect based on the standard assessment categories in each aspect tested. The Google Maps application is superior than other three applications based on four of the five aspects tested: functionality, effectiveness, efficiency, reliability, usability.